Peran Keluarga dalam Membangun Kesadaran Sosial pada Mahasiswa Pendidikan Sosiologi Universitas Sultan Ageng Tirtayasa - Nadhirah, Siti Hasna; Lindawati, Yustika Irfani (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
The family is the first social unit that shapes an individual's identity and character through blood relations, marriage, or adoption. In the context of building social awareness, the family plays an important role in instilling social values, forming moral character, and teaching social responsibility. This research aims to examine the role of the family in building social awareness among students in the Sociology Education Study Program at Sultan Ageng Tirtayasa University. This research uses a qualitative approach with a case study method involving in-depth interviews and observations of sociology education students at Sultan Ageng Tirtayasa University. The research results show that the family acts as the first socialization agent to provide basic social values, such as concern for the environment, justice and empathy. Apart from that, communication and interaction patterns within the family also influence the development of students' critical attitudes towards existing social issues. This research concludes that the family has a significant influence in shaping students' social awareness, which contributes to the learning process in sociology education at the tertiary level.